The Comparison of Dietary Behaviors among Rural Controlled and Uncontrolled Hypertensive Patients. (19th July 2016) - Kamran, Aziz; Shekarchi, Ali Akbar; Sharifian, Elham; Heydari, Heshmatolah
Abstract : Nutrition is a dominant peripheral factor in increasing blood pressure; however, little information is available about the nutritional status of hypertensive patients in Iran. This study aimed to compare nutritional behaviors of the rural controlled and uncontrolled hypertensive patients and to determine the predictive power of nutritional behaviors from blood pressure. This cross-sectional study was conducted on 671 rural hypertensive patients, using multistage random sampling method in Ardabil city in 2013. Data were collected by a 3-day food record questionnaire. Nutritional data were extracted by Nutritionist 4 software and analyzed by the SPSS 18 software using Pearson correlation, multiple linear regression, ANOVA, and independent t -test. A significant difference was observed in the means of fat intake, cholesterol, saturated fat, sodium, energy, calcium, vitamin C, fiber, and nutritional knowledge between controlled and uncontrolled groups. In the controlled group, sodium, saturated fats, vitamin C, calcium, and energy intake explained 30.6% of the variations in blood pressure and, in the uncontrolled group, sodium, carbohydrate, fiber intake, and nutritional knowledge explained 83% of the variations in blood pressure. There was a significant difference in the nutritional behavior between the two groups and changes in blood pressure could be explained significantly by nutritional behaviors.